An overview on biodegradation of polystyrene and modified polystyrene: the microbial approach. (17th February 2018) - Ho, Ba Thanh; Roberts, Timothy K.; Lucas, Steven
Abstract: Polystyrene is a widely used plastic in many aspects of human life and in industries due to its useful characteristics of low cost, light weight, ease of manufacture, versatility, thermal efficiency, durability, and moisture resistance. However, polystyrene is very stable and extremely hard to degrade in the environment after disposal. Polystyrene can be used as a carbon source for microorganisms similar to many other hydrocarbons. The ability of microorganisms to use polystyrene as a carbon source has been recently established. However, the high molecular weight of polystyrene limits its use as a substrate for enzymatic reactions to take place. In this paper, we review studies on biodegradation of polystyrene to give an overview and direction for future studies.